PENGEMBANGAN PERANGKAT PETUNJUK PRAKTIKUM BERBASIS JIGSAW MELALUI PENDEKATAN PROBING PADA MATA KULIAH TEKNIK LABORATORIUM - St Rahmadani; Ryan Humardani Syam Pratomo (Jurnal Biotek, 2020)
The aim of this research is to develop laboratory work guidance based on the jigsaw learning method combined with the probing approach. This research also aimed to analyze the characteristics and properness of the developed product. The research referred to the previous model that was designed by Borg and Gall. The research was conducted from a preliminary study to trial test empirically and carried out with the one group pre-test post-test design. The product was examined by two validators resulting in 4,59 and 4,82 in the category of very good. The product also tested restrictedly to 10 students with different competencies (high, moderate, and low). There was 83% with high competency, and 80% with both moderate and low competency. The collected data were statistically analyzed by t-Paired test in SPSS 23 version for windows showed the value of significance is 0.000 and lower than 0,05. It implies that the pre-test scores are significantly different from the post-test meaning that the product is available to use.